PEMANFAATAN SQLMAP UNTUK DETEKSI SQL INJECTION PADA SITUS WEB - Salsabila, Hulwa; Fithra, Raka Fazah (Universitas Lampung, 2025)
SQL Injection is a serious threat to the security of dynamic websites widely used on the internet. This attack can expose sensitive information and compromise system integrity. Therefore, this research was conducted to identify and exploit vulnerabilities in websites using the SQLMAP tool. This tool allows for scanning and extracting data from databases vulnerable to SQL Injection attacks. The research started by scanning the website to identify the database in use, followed by exploring the tables, and finally dumping data from the selected table. The results of the study show that SQLMAP can be effectively used to detect and exploit vulnerabilities in websites with SQL Injection flaws. Although effective, its use requires a deep technical understanding of SQL and server configurations. These findings are significant in the context of website security testing and contribute to the development of more effective tools to detect and address potential SQL Injection attacks. This research is expected to raise awareness and understanding of the importance of securing websites against SQL Injection attacks.